Development of RP-HPLC method for the estimation of Rasagiline mesylate in bulk and tablet dosage forms - Raj, Napa Delhi; Rao, Abburu Rukmangada; Bhimanadhuni, Chusena Narasimharaju (International Current Pharmaceutical Journal, 2012)
A simple RP-HPLC method for the determination of Rasagiline Mesylate in bulk and tablet dosage form was developed. Numerous HPLC conditions were tested for determination of rasagiline. The best result was achieved by using Purosphere star RP-18, (150×4.6mm), 5µm column and a mobile phase consisting of Potassium Orthophosphate: Acetonitrile (60:40 v/v) adjusted to pH 7.0(±0.05) with Ammonia solution, a flow rate of 1.5 ml/min with ultraviolet detection at 210nm. The correlation coefficients for calibration curves within the detection range of 5-30µg/ml were 0.9993. The within and between-day precision was determined for both retention time and peak area. The retention time of rasagiline is 6.0 minutes. DOI: http://dx.doi.org/10.3329/icpj.v1i9.11620 International Current Pharmaceutical Journal 2012, 1(9): 285-287